(untitled) (Revista Bioética, 2014)
The relationship between health professionals and users is a challenging theme for the reorganization of public health services. The objective was to discuss the professional-user members on care and health education issues in the Family Health Strategy (FHS) context using the Contractualist Bioethics perspective. As for the method, a literature and critique review was done in the Virtual Library of Health Ethical journals. The ethics issues are part of the care and health education in the FHS. The contractualist model is the most desirable related to the professional and users of the health services, since it involves commitment of both parts. Unlikely, the priest, engineer and high school models should be avoided because they characterize domination, accommodation, negotiation and submission. The host was suggested as a tool for confronting the undesirable models. The care process and health education should be based on the Contractualist model between the professional and a user. The real interpersonal relationship impacts positively to workers and users, since it suggests empowerment of those involved in the family health work process.